Cataract surgery and environmental sustainability: a comparative analysis of single-use versus reusable cassettes in phacoemulsification - Oscar Kallay; Rayane Sadad; Ahmed Zafzafi; Elie Motulsky (BMJ Open Ophthalmology)
Objective To compare sustainability, financial implications and surgical efficiency of two phacoemulsification cassette systems for cataract surgery: a machine with single-use cassettes and another with daily, reusable ones.Methods Observational study involving retrospective cataract surgery data collection at the Centre Médical de l’Alliance, Braine-l’Alleud, Belgium, a tertiary eye care centre. Information on cassette weight, quantities and transport volume was obtained from routine procedures and purchasing records. The costs for each machine were calculated by reviewing the invoices received from the accounting department.Results We found significant differences across comparisons. The reusable cassette machine, when compared with the single-use machine, used 306.7 kg less plastic (75.3% reduction), required 2494 m3 less storage per 1000 surgeries (67.7% decrease) and cost €54.16 less per 10 procedures (16.9% reduction). The machine with daily reusable cassettes also exhibited a 7-minute priming time advantage for 10 procedures, reducing downtime between cases.Conclusions Our findings underscore the benefits of adopting reusable cassette systems: reduced plastic consumption, storage volume and priming time, as well as enhanced efficiency and cost-savings. Healthcare professionals and institutions are encouraged to embrace environmentally conscious initiatives. The use of reusable cassette systems for cataract surgeries offers a pathway to sustainable practices.